Pengaruh Lama Fermentasi Dan Konsentrasi Ragi Terhadap Mutu Tape Ubi Jalar Ungu (Ipomoea batatas L.) Varietas Ayamurasaki - Ardiansyah, Adi; Kalsum, Umi; Nasirudin, Mohamad (Exact Papers in Compilation (EPiC), 2022)
An experiment was arranged to determine the effect of fermentation time and yeast concentration on the color, taste and aroma of sweet potato tape (Ipomoea batatas L.) Ayamurasaki variety. This research was conducted in Tanjunggunung village, Peterongan Jombang sub-district, in July-November 2019. The study was arranged using a Randomized Block Design (RAK) and repeated three times with the following treatments: F1K1 : (48 hours fermentation yeast concentration 0.5%), F1K2 (48 hours fermentation with 1% yeast concentration), F1K3 (48 hours fermentation with 1.5% yeast concentration) F2K1 (48 hours fermentation with 0.5% yeast concentration), F2K2 (48 hours fermentation with 1% yeast concentration) F2K3 (48 hours fermentation yeast concentration 1.5%), F3K1 (48 hours fermentation yeast concentration 0.5%), F3K2 (48 hours fermentation yeast 1% concentration), F3K3 (48 hours fermentation yeast concentration 1.5%). The results of the analysis of variance showed that yeast concentration and fermentation time had a very significant effect on all variables except the color variable. The best treatment value is F1K1 and the lowest value treatment is F3K3. The longer the fermentation and the greater the concentration of yeast given, the acidity of the tape becomes very sour.